Back Cover: Recent applications of plant cell culture technology in cosmetics and foods. Issue 3 (2nd March 2021) - Krasteva, Gergana; Georgiev, Vasil; Pavlov, Atanas
Abstract : DOI: 10.1002/elsc.202000078 The cover picture shows a process of submerged cultivation of hairy root culture of red beet in a stirred tank bioreactor, different types Beta vulgaris L. in vitro cultures and their ploidity levels. Biosynthesis of red betacyanins and yellow betaxanthins, used as food colorants and antioxidant additives, was found to be related with the level of differentiation of developed in vitro systems and underwent cycles of endoreduplication. Among the investigated red beet in vitro cultures, hairy roots showed the best potential for production of betalains. For details see article DOI 10.1002/elsc.202000078 on page 68.